The relative importance of local labour market conditions and pupil attainment on post-compulsory schooling decisions - Elena Meschi; Joanna Swaffield; Anna Vignoles (Institute for the Study of Labor (IZA), 2011)
This paper assesses the relative importance of local labour market conditions and pupil educational attainment as primary determinants of the post-compulsory schooling decision. Using a nested logit model we formally incorporate the structured and sequential decision process pupils engage with. Our findings show that, on average, the key drivers of the schooling decision are pupil educational attainment and parental aspirations rather than local labour market conditions. However, there is some evidence that higher local unemployment rates encourage males to invest in education, and that interactions with educational attainment suggest local labour market conditions impact heterogeneously across the pupil population.
urn:nbn:de:101:1-2012010913631
Keywords: I21; J18; J24; 330; post-compulsory education; local labour markets; parental aspirations; educational attainment; nested logit; Bildungsverhalten; Bildungsniveau; Regionaler Arbeitsmarkt; Familiensoziologie; Schätzung; Großbritannien